2016
DOI: 10.1161/jaha.116.003200
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Valve Morphology on the Prevalence of Coronary Artery Disease: A Systematic Review and Meta‐Analysis

Abstract: BackgroundLiterature studies suggested a lower prevalence of coronary artery disease (CAD) in bicuspid aortic valve (BAV) than in tricuspid aortic valve (TAV) patients. However, this finding has been challenged. We performed a meta‐analysis to assess whether aortic valve morphology has a different association with CAD, concomitant coronary artery bypass grafting (CABG), and postoperative mortality.Methods and ResultsDetailed search was conducted according to the PRISMA (Preferred Reporting Items for Systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Mechanisms of intra-operative inflammation resulting in vascular injury mediated by cytokines such as TGF-β1 have been proposed but require further investigation 38 . While reports on the prevalence of CAD in adults with aortic valve malformations are variable 39 , bicuspid aortic valve has been associated with higher incidence of CAD than expected for age 40 and with underlying vasculopathies that predispose to CAD 41 . Variation at the TEX41 locus discovered through genome-wide association study has recently been associated with both bicuspid aortic valve and CAD 42 , further underscoring the potential for a shared genetic basis of congenital heart malformations and acquired cardiovascular disease.…”
Section: Discussionmentioning
confidence: 98%
“…Mechanisms of intra-operative inflammation resulting in vascular injury mediated by cytokines such as TGF-β1 have been proposed but require further investigation 38 . While reports on the prevalence of CAD in adults with aortic valve malformations are variable 39 , bicuspid aortic valve has been associated with higher incidence of CAD than expected for age 40 and with underlying vasculopathies that predispose to CAD 41 . Variation at the TEX41 locus discovered through genome-wide association study has recently been associated with both bicuspid aortic valve and CAD 42 , further underscoring the potential for a shared genetic basis of congenital heart malformations and acquired cardiovascular disease.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were seen in a previous systematic review in which age was also an important confounder. 60 This indicates no clinical differences in CAD and coronary revascularization between BAV and TAV patients. Although not significantly different, the prevalence of CAD risk factors was high in both groups, indicating that an individual approach for treating these comorbidities is important for both groups.…”
Section: Discussionmentioning
confidence: 92%
“…A recent systematic review reported that at the time of AVR, in all 16 studies the need for concomitant CABG was lower for BAV than for TAV. A meta-regression analysis showed that this was explained by younger age and lower prevalence of diabetes in BAV compared to TAV patients [ 18 ]. In contrast, our study demonstrated that native valve anatomy determined the need for CABG in addition to age and hypercholesterolaemia.…”
Section: Discussionmentioning
confidence: 99%